Effect of chitosan concentration on gelation of chitosan/ nanohydroxyapatite/ Na2CO3 composite - Perera, P. S. D.; Adikary, S. U. (Faculty of Science, University of Kelaniya, Sri Lanka., 2021)
An injectable in situ forming chitosan/nanohydroxyapatite/Na2CO3 (chitosan/nHA/Na2CO3) composite gel was investigated to study its gelation time. This study used locally synthesized chitosan as the polymer material to synthesis chitosan thermosensitive gel. The sol-gel phase transition was primarily examined. We found that chitosan/nHA/Na2CO3 sol with 1.6% of chitosan has required coagulant performance. The lower concentration of chitosan had reported longer gelation behavior while the higher concentration of chitosan exhibited unstable behavior. The surface morphology of the chitosan/nHA/Na2CO3 composite depicts the structure of polymer gel composite. Scanning electron microscope confirmed the presence of hydroxyapatite on the chitosan matrix, indicating chitosan/nHA polymer gel composite was a suitable polymer substrate for injectable gel systems. EDX spectra shows the Ca/P value of the synthesized nano- hydroxyapatite to be 1.67. It was confirming the presence of nanohydroxyapatite on the composite. The kinetic study of this gelation process will make it possible to adjust the properties of the chitosan/nHA/Na2CO3 composite gel. The gelation temperature was carried out at body temperature (37 0C).
Keywords: Chitosan, Chitosan/nHA/Na2CO3 composite, nanohydroxyapatite.